The Impact of the Implementation of Good Governance on the Improvement of the Quality of Education in Local Governments - Arsyad, Arsyad; Samiri, Muliani; Nilwana, Andi (Department of Government Studies, Universitas Muhammadiyah Buton., 2024)
This study aims to examine the impact of good governance implementation on enhancing educational quality at Vocational High School 3 Pare-Pare. This study employed a quantitative methodology with a descriptive design, whereby data were gathered through questionnaires and analyzed using the Statistical Package for the Social Sciences (SPSS) software. Validity tests were conducted to ensure the reliability of the data, and regression analysis was employed to identify the relationship between the independent variable (good governance implementation) and the dependent variable (education quality). The results indicated that 79 percent of the variation in educational quality could be attributed to implementing good governance, thereby demonstrating that good governance considerably influences enhancing academic quality. Nevertheless, the model could not account for 21 percent of the observed variation, indicating that additional factors may be at play. The findings support the proposition that implementing good governance principles, such as transparency, accountability, and participation, is a crucial element in the effective management of educational institutions. The practical implications of this study are that schools must enhance their enforcement of the law and their accountability and that all school components must be included in the planning and evaluation of programs. School principals are expected to establish specialized teams, such as TPMS, to guarantee uniform implementation. Nevertheless, this study is not without limitations. Firstly, the focus on a single school may limit the generalizability of the results. Secondly, further research is needed to explore other factors influencing education quality. Thirdly, this study provides a basis for developing better governance policies in the education sector.